BURUH ANAK:MAMPUKAH KEBIJAKAN NEGARA MELINDUNGI? - APRIANI, FAJAR (PUBLISIA (Jurnal Ilmu Administrasi Publik), 2016)
The phenomenon of child labor in developing countries often have yet to be resolved, especially child labor in the informal sector. Children are the next generation of the nation, so that should get the fulfillment of their rights by the state and the family environment that feasible. Children have the right to acquire education, develop personality and potential, as well as protection from violence and discrimination. However, the strong patriarchal ideology, neoliberalismâs influence and the discrimination against the child in the field of education, particularly for girls, as well as the still weak state policy in protecting child labor, making this problem up to now has not been able to solve. The problem of poverty is often understood as the basis of the causes of child labor issues. But a more serious cause is in fact concerns the responsibility of the countryâs top that does not satisfy the rights of the child, in particular in terms of education.